2000
DOI: 10.1161/01.cir.102.18.2214
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative General Theory for Periodic Breathing in Chronic Heart Failure and its Clinical Implications

Abstract: Background-In patients with chronic heart failure (CHF), periodic breathing (PB) predicts poor prognosis. Clinical studies have identified numerous risk factors for PB (which also includes Cheyne-Stokes respiration). Computer simulations have shown that oscillations can arise from delayed negative feedback. However, no simple general theory quantitatively explains PB and its mechanisms of treatment using widely-understood clinical concepts. Therefore, we introduce a new approach to the quantitative analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
140
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 168 publications
(150 citation statements)
references
References 39 publications
9
140
0
1
Order By: Relevance
“…The cyclelength in our patients with severe CSA (48 s), although higher than the cycle-length reported in patients with idiopathic CSA and normal ventricular function (35 s), 13 is significantly lower than the cycle-length reported in patients with CSA and heart failure (69 s). 13,24 In our present study, the cycle-length was similar for all patients, thus confirming that the degree of hemodynamic dysfunction reflected by this index is equally present in these 3 groups and, therefore, is not the primary factor inducing CSA in our patients.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The cyclelength in our patients with severe CSA (48 s), although higher than the cycle-length reported in patients with idiopathic CSA and normal ventricular function (35 s), 13 is significantly lower than the cycle-length reported in patients with CSA and heart failure (69 s). 13,24 In our present study, the cycle-length was similar for all patients, thus confirming that the degree of hemodynamic dysfunction reflected by this index is equally present in these 3 groups and, therefore, is not the primary factor inducing CSA in our patients.…”
Section: Discussionsupporting
confidence: 82%
“…In patients with overt heart failure, CSA correlated with pulmonary capillary wedge pressure, as measured by invasive 22 and noninvasive 23,24 approaches. In our present study of patients with LV dysfunction without overt heart failure, the presence and severity of CSA was not associated with increased ventricular impairment or hemodynamic indices of increased filling pressure (Figure 2).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although CSB has been known for many years to be associated with HF, 8,9 its mechanism, prognostic implications, and possible therapies are still controversial. [10][11][12][13] Although in this current study we concentrated solely on a specific pattern of central sleep disturbance, namely CSB, other forms of sleep apnea have been identified in HF patients, including obstructive and central apneas. 6,12,14 A few studies of HF patients suggested that high AHI, obstructive, and central apneas are all associated with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of models of the cardiovascular and respiratory systems have been constructed [8,9,10,11,16,18,20,24,26,28,31,39,42]. The models that are most related to our research mathematically use…”
mentioning
confidence: 99%